Business consulting – Derco Perú - Concha Huerta, Antony William (2024)
This work addresses the problems of the DERCO company at its different levels, making a diagnosis where the main problem found is "Deficient service process in DERCO service workshops", since it is a problem that involves several aspects of improvement such as the vehicle maintenance process, quality control of the processes that are developed, reversing the high turnover of DERCO's operational staff, among others. This work has five chapters, the first chapter addresses the general situation of the company, presentation of the company, INCHCAPE business model, PESTEL analysis, analysis of the industrial sector, analysis of Porter's Five Forces. In chapter two, the work methodology and list of problems of the company under study are presented, the problems identified being (1) Deficient service process in service workshops (2) Deficient vehicle maintenance process, (3) Low level of DERCO customer retention, (4) High turnover of technical staff and (5) Deficient quality control. Likewise, a Complexity versus Benefit Matrix is carried out. Finally, the main problem is considered: “Poor service workshop service process”. In chapter three, the causes of the main problem are determined, and the root cause prioritization matrix is developed. Considering the feasibility and benefit criteria, the main causes of the identified problem are obtained as results, which are grouped according to the type of activity. Starting with “Operations”, where the “Poor appointment management process” has a total score of 16, the “Poor customer reception process” of 15 and “Poor supply process” of 15. Followed by the causes of “Operational HR” which obtains a score of 16 for poorly trained personnel, as well as the causes of “Marketing” whose problem “Activities focused on attracting new clients” has a total of 15 points. Finally, at the level of “Administration” causes, the “low level of organizational culture” of DERCO is considered, with a score of 15. viii In the fourth chapter, the alternative solutions are presented, then the plan for improving the post-sale service processes is considered, considering that service in the service workshops involves more than one process such as: (1) Appointment management, (2) vehicle reception (3) maintenance (4) supply (5) road test (6) washing and drying (7) Cash register – billing (8) Delivery of the vehicle, which take a total of 5 to 7 hours, depending on whether it is minor or major maintenance, which contain different services. Likewise, the plan for renewal and maintenance of equipment and tools and the Marketing Plan to retain current and former customers are considered. Finally, it can be concluded that the most convenient solution alternatives to achieve reversing the main problem are (1) The service workshop improvement plan with a rating of 3.7, (2) the complementary marketing plan to retain current and former customers with 3.10 and (3) the training plan for operational staff with 3.1, so a combined proposal was made involving the 3 alternatives. In the fifth chapter, the Implementation Plan and key success factors, balanced scorecard, implementation plan and budget are developed. Finally, the indicators at the optimistic scenario level, the NPV is 1,020,881 soles with an IRR of 249.40%, B/C ratio 6.834 and a Payback (months) of 5,393. While, in the moderate scenario, the NPV is 637,203 soles with an IRR of 168.0%, B/C ratio 4.641 and a Payback (months) of 7.691. Finally, in the pessimistic scenario the NPV is 253, 525 soles with an IRR of 83.25%, B/C ratio 2.449 and a Payback (months) of 21.40.